Perkembangan Riset Keterampilan Sosial Siswa SD di Indonesia: Tinjauan Literatur Sistematis (2020-2025): The Development of Social Skills Research on Elementary School Students in Indonesia: A Systematic Literature Review (2020-2025) - Shoffy Izzatur Rahmah; Linda Zakiah; Syarif Sumantri (ITScience (Information Technology and Science), 2026)
Social skills are important competencies that shape the quality of interactions, adaptability, and the holistic development of elementary school students in social life. This study aims to map research development trends, identify dominant methodological approaches, and synthesize factors influencing the social skills of elementary school students in Indonesia in the 2020–2025 period. The study used a Systematic Literature Review (SLR) approach with systematic procedures to identify, select, and analyze articles. A total of 20 articles that met the inclusion criteria were obtained from three main databases: Google Scholar, ERIC, and Garuda Kemdikbud. Data were analyzed qualitatively using a synthesis matrix and thematic analysis to identify patterns in research findings. The study's results indicate an increase in research publications on the social skills of elementary school students during the 2020–2025 period. In addition, the most dominant research method used was a descriptive qualitative approach, followed by quantitative and mixed methods. Thematic analysis also revealed five main factors influencing students' social skills: the use of innovative learning models, the quality of classroom management, the integration of local wisdom values, the impact of digital technology, and the level of family involvement in children's education. These findings indicate that developing elementary school students' social skills requires a holistic, collaborative approach that integrates teachers, families, and the social environment to support students' optimal social development.